Constructions of Dense Lattices over Number Fields - Andrade, A.a. [UNESP]; Ferrari, A.j. [UNESP]; Interlando, J.c.; Araujo, R. R. (Sociedade Brasileira de MatemÃ¡tica Aplicada e Computacional, 2020)
In this work, we present constructions of algebraic lattices in Euclidean space with optimal center density in dimensions 2;3;4;5;6;8 and 12, which are rotated versions of the lattices Î›n , for n=2,3,4,5,6,8 and K 12. These algebraic lattices are constructed through canonical homomorphism via â„¤-modules of the ring of algebraic integers of a number field.

Neste trabalho, apresentamos construÃ§Ãµoes de reticulados algÃ©bricos no espaÃ§o euclidiano com densidade central Ã³tima nas dimensÃµes 2, 3, 4, 5, 6, 8 e 12, que sÃ£o versÃµes rotacionadas dos reticulados Î›n , para n=2,3,4,5,6,8 e K 12, onde esses reticulados algÃ©bricos sÃ£o construÃdos atravÃ©s do homomorfismo canÃ´nico via â„¤-mÃ³dulos do anel de inteiros algÃ©bricos de um corpo de nÃºmeros.
Keywords: algebric lattices; number fields; sphere packings; reticulados algébricos; corpos de números; empacotamento esférico